The last kids on Earth and the zombie parade! - Brallier, Max (Viking, 2016)
After the monster apocalypse, Jack Sullivan has been having an awesome time living in a tree house with his three best friends. But when zombies start mysteriously disappearing, Jack and his friends suspect that an extremely evil force is at work.